Multiple organ dysfunction syndrome associated with hyperglycemia in children requiring intensive care - Hendy Halim; Ida Bagus Gede Suparyatha; I Made Arimbawa; I Nyoman Budi Hartawan (Paediatrica Indonesiana, 2015)
Background Hyperglycemia can be caused by three or more organ dysfunctions and occurs in children requiring intensive care in the first 48 hours. Blood sugar level higher than 140 mg/dl is considered as hyperglycemia in children requiring intensive care.Objective To determine the association between multiple organ dysfunction syndrome (MODS) in children requiring intensive care and hyperglycemia with blood sugar level higher than 140 mg/dl.Methods This case control study without matching was conducted on children aged 1 month-12 years from pediatric ward at Sanglah hospital during June-August 2012. We used consecutive sampling to recruit subjects, which then were screened by Pediatric Risk of Hospital Admission (PRISA) 2 score. All subjects were enrolled for blood sugar test, then divided into 2 groups; hyperglycemia with blood sugar level > 140 mg/dl as case and normoglycemia as control. We used organ dysfunction criteria to determine multiple organ dysfunction. The association between MODS and hyperglycemia was assessed by Chi-square test with 95% confidence interval and a statistical significance value of P < 0.05.Results Fifty two subjects were enrolled in this study. We excluded two subjects, hence each group consisted of 25 subjects. We found 18 subjects under and 7 subjects above five years old in hyperglycemia group. The association between multiple organ dysfunction and hyperglycemia was significant with an odds ratio of 10 (95% CI 3 to 38), P < 0.0001.Conclusion Multiple organ dysfunction syndrome had a significant association with hyperglycemia. Multiple organ dysfunction syndrome with hyperglycemia occurs ten times greater than with normoglycemia.